Restoration of periodontitis-induced bone defects with multifunctional barrier membranes by alleviating oxidative stress and remodelling macrophage metabolism - Han, Lei; Huang, Jimin; Zhang, Zhiyong; Feng, Guijuan; Zheng, Yi; Zhu, Yufang; Li, Huang (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
Periodontal bone regeneration is hindered by the inflammatory microenvironment with high reactive oxygen species levels. Current barrier membranes lack sufficient antioxidative and bioactive properties, leading to poor bone regeneration. To overcome this, a novel guided bone regeneration membrane was developed by combining manganese-incorporated bioactive glass (MnBG) with biodegradable poly(lactic-co-glycolic acid (PLGA) and polycaprolactone (PCL). This PLGA/PCL/MnBG (PPMnBG) membrane could protect bone marrow mesenchymal stem cells (BMMSCs) and RAW264.7 cells from oxidative damage, promote cell proliferation, adhesion, and osteogenic differentiation, and inhibited M1 macrophage polarization. It enhanced macrophage oxidative stress resistance and suppressed glycolysis in M1 macrophages via the JAK-STAT1/NLRP3 pathway, reducing inflammation. In vivo studies using SD rat alveolar bone defect confirmed the membrane's efficacy in alleviating oxidative stress, reprogramming macrophage metabolism, and promoting bone regeneration. These findings highlighted the PPMnBG membrane's potential in treating inflammatory alveolar bone defects by mitigating oxidative stress, enhancing osteogenesis, and modulating macrophage metabolism. •PPMnBG-membrane composed of Mn-incorporated BG microspheres (MnBG) and biodegradable polymers of PLGA and PCL were reported.•PPMnBG membranes exhibited excellent ROS scavenging performance due to the catalytic activity of MnBG.•PPMnBG membranes could protect cells from oxidative damage and inhibited M1 macrophage polarization.•PPMnBG membrane enhanced macrophage oxidative stress resistance and suppressed glycolysis via the JAK-STAT1/NLRP3 pathway.•PPMnBG membranes could reduce oxidative stress and remodel macrophage metabolism for bone regeneration in periodontitis.